PUSAT PELATIHAN PEMUDA DAN PENDIDIKAN ANAK (SEKOLAH MINGGU) GEREJA BETHEL INDONESIA KOTA GORONTALO - Rahel Wanimbo (Jurnal Teknik Sipil, Arsitek, Perencanaan Wilayah (J-TSIAP), 2022)
This study aims to design and design a youth training center and children's education at Bethel Indonesia church in Gorontalo City using a psychological architectural approach. Each of these Christian denominations has its own church. One of them in the province of Gorontalo is the Indonesian Bethel Church (GBI), a Protestant Christian church group or synod in Indonesia. As a place of worship, Bethel Church Indonesia (GBI) needs physical facilities that can accommodate all the congregation's worship activities that require peace in achieving solemn worship with God and can accommodate other spiritual activities of all age groups including youth and children designing a youth training center and the education of Bethel church children can become a forum for the needs of Christians in Gorontalo district. The location of the Bethel Indonesia church's youth and education training center, Gorontalo district, is on Jl. Idris Dunggio, Kayu Merah village, Limboto sub-district, with an area of ​​±4.3 ha. The site has several potential advantages, including the location of the site adjacent to Christian worship facilities, Limboto towers of majesty park, government center, education center and residents' homes. Emphasizing the relationship between user behavior and the environment while in a building will create beauty in a work, focusing on aspects of human psychology in architecture that affect vision: Shape of space, Lighting and Color.